Marine Microbial Food Web Networks During Phytoplankton Bloom and Non-bloom Periods: Warming Favors Smaller Organism Interactions and Intensifies Trophic Cascade - Trombetta, Thomas; Vidussi, Francesca; Roques, Cécile; Scotti, Marco; Mostajir, Behzad (Frontiers in Microbiology, 2020)
Microbial food web organisms are at the base of the functioning of pelagic ecosystems and support the whole marine food web. They are very reactive to environmental changes and their interactions are modified in response to different productive periods such as phytoplankton bloom and non-bloom as well as contrasted climatic years. To study ecological associations, identify potential interactions between microorganisms and study the structure of the microbial food web in coastal waters, a weekly monitoring was carried out in the Thau Lagoon on the French Mediterranean coast. The monitoring lasted from winter to late spring during two contrasting climatic years, a typical Mediterranean (2015) and a year with an extreme warm winter (2016). Correlation networks comprising 110 groups/taxa/species were constructed to characterize potential possible interactions between the microorganisms during bloom and non-bloom periods. Complex correlation networks during the bloom and dominated by negative intraguild correlations and positive correlations of phytoplankton with bacteria. Such pattern can be interpreted as a dominance of competition and mutualism. In contrast, correlation networks during the non-bloom period were less complex and mostly dominated by tintinnids associations with bacteria mostly referring to potential feeding on bacteria, which suggests a shift of biomass transfer from phytoplankton-dominated food webs during bloom to more bacterioplankton-based food webs during non-bloom. Inter-annual climatic conditions significantly modified the structure of microbial food webs. The warmer year favored relationships among smaller group/taxa/species at the expense of large phytoplankton and ciliates, possibly due to an intensification of the trophic cascade with a potential shift in energy circulation through microbial food web. Our study compares a typical Mediterranean spring with another mimicking the prospected intensification of global warming; if such consideration holds true, the dominance of future coastal marine ecosystems will be shifted from the highly productive herbivorous food web to the less productive microbial food web.